The Empowerment of Defense Areas in a Changeover Perspective - Samego, Indria (The Republic of Indonesia Defense University, 2015)
In accordance with the keyword in this article, â€œcontextualisationâ€, this article examines the problem of state defence system in the dynamic and contextual perspective. Taking in consideration the existing structural environment changes, related legislations and their implementations should be updated from time to time. This is very important not only for decision makers but also for all related stakeholders.. When non-military power plays a greater role in determining the countryâ€™s defence posture, defence planners would have to shift their attention from hard power calculations to diplomacy and the development of other elements of soft power